Maturação e indicadores do ponto de colheita de uva ‘Arra 15’ no Submédio do Vale do São Francisco - Cruz, Maisa de Macedo (Universidade Federal Rural do Semi-Árido, 2018)
The viticulture developed in the region of the Valley of the São Francisco has been emphasizing in the last years by the introduction of new cultivars, diversifying the offer for the consumption in natura. However, the newly introduced cultivars demand adjustments in the management and the overcoming of problems related to the quality of the bunches, both due to the lack of a production system proper to the region. Thus, the objective of this work was to characterize the maturation and to define the appropriate point of harvest of the table grape of the cultivar Arra 15® in the conditions of the Submedia of the Valley of the São Francisco. The fruits came from the Serenissima farm, located in the municipality of Lagoa Grande, PE. Two productive cycles of the year 2017 were evaluated. In both, curls of the beginning of the maturation were evaluated, characterized by the beginning of the softening of the berries, until the complete maturation. The experimental design was in randomized blocks, with five replications, consisting of five bunches, of three plants / plot. The samples were collected at 51, 58, 61, 66, 69 and 75 days after fruiting (daf) for the first cycle, and for the second cycle at 48, 55, 62, 69, 76 and 83 daf. The Arra 15® table grape was harvested at 75 daf (108 days after pruning) for fruits harvested in the first half of the year and at 83 daf (124 days after pruning) for fruits harvested in the second half. The variables bunch mass, berries mass, loam mass and bark elasticity in the second cycle showed a reduction in the values at the end of maturation, signaling that the harvest could have been anticipated. Changes in bunch mass, berry mass, color angle (H *), firmness, bark elasticity, soluble solids content (SS), total soluble sugars (AST), titratable acidity (AT) and ABTS were representative in evolution and can be used to determine the harvest point. Climatic factors, mainly temperature and solar radiation, influenced berry mass, H *, SS, AST, AT, yellow flavonoids and total extractable polyphenols. The Arra 15 cultiv cultivar presented SS, AT, firmness and resistance of the berry to the compression force that meet the marketing standards
Maturation and indicators of harvest point in grape ‘Arra 15’ in São Francisco Valley Sub-medium
Keywords: Vitis vinifera L.; Amadurecimento; Viticultura tropical; Uva de mesa; Vinitis vinifera L.; Maturation; Tropical viniculture; Table grape; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA